2023
DOI: 10.1007/s00223-023-01066-3
|View full text |Cite
|
Sign up to set email alerts
|

Bone Microarchitecture and Strength Changes During Teriparatide and Zoledronic Acid Treatment in a Patient with Pregnancy and Lactation-Associated Osteoporosis with Multiple Vertebral Fractures

Abstract: Pregnancy- and lactation-associated osteoporosis (PLO) is a rare form of osteoporosis, of which the pathogenesis and best treatment options are unclear. In this report, we describe the case of a 34-year old woman diagnosed with severe osteoporosis and multiple vertebral fractures after her first pregnancy, who was subsequently treated with teriparatide (TPTD) and zoledronic acid (ZA). We describe the clinical features, imaging examination, and genetic analysis. Substantial improvements were observed in areal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Overall, in addition to 24 new (single) case reports [23,44,51,[55][56][57][58][59][60][61][62][63][64][65][66][67][68], we identified 12 original studies (with at least 6 patients with PAO/LAO per study): 1 study was published in 2023 (within the first 3 months of the year), 5 were published in 2022, and 6 in 2021. Except for one survey [43], these were retrospective cohorts (one being a nationwide study in Japan) [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, in addition to 24 new (single) case reports [23,44,51,[55][56][57][58][59][60][61][62][63][64][65][66][67][68], we identified 12 original studies (with at least 6 patients with PAO/LAO per study): 1 study was published in 2023 (within the first 3 months of the year), 5 were published in 2022, and 6 in 2021. Except for one survey [43], these were retrospective cohorts (one being a nationwide study in Japan) [41].…”
Section: Discussionmentioning
confidence: 99%
“…A 34-year-old female was treated with TPT followed by ZOL (in a recent case published in 2023) with a good outcome registered by central DXA and high-resolution peripheral quantitative CT scans, but reported values remained lower than similar controls at 40 months after delivery. Genetic tests (considering the traditional panel for monogenic osteoporosis) were negative, thus being suggestive of a polygenic involvement in the pathogenic loop of osteoporosis [58].…”
Section: Case Reports Of Laomentioning
confidence: 99%
“…Pregnancy and lactation‐associated osteoporosis (PLO) is an uncommon condition of skeletal fragility that affects women during pregnancy or postpartum period. It presents with back pain and vertebral compression fractures 2 . The management of PLO is challenging, but early diagnosis, stopping breastfeeding, treatment of anti‐osteoporosis medicine, and regular follow‐ups are necessary for the prevention of fractures and to increase the mother's quality of life 3,4 .…”
Section: Introductionmentioning
confidence: 99%
“…It presents with back pain and vertebral compression fractures. 2 The management of PLO is challenging, but early diagnosis, stopping breastfeeding, treatment of anti‐osteoporosis medicine, and regular follow‐ups are necessary for the prevention of fractures and to increase the mother's quality of life. 3 , 4 We present a very rare case of a 22‐year‐old woman, who has been diagnosed with PLO 5 months after delivering her child.…”
Section: Introductionmentioning
confidence: 99%
“…It has a high a nity for mineralized bone and can selectively act on bone to inhibit osteoclast activity and induce osteoclast apoptosis, thereby inhibiting bone resorption and improving bone density, thereby reducing revision rate and prolonging the service life of prosthetics. Reduces the risk of recurrent fractures [3][4][5][6]. It has been reported that a single injection of ZA can effectively improve bone mineral density (BMD) for at least 12 months [7] and has a positive effect on male BMD [8].…”
Section: Introductionmentioning
confidence: 99%